DOI: 10.11606/t.75.2015.tde-10092015-110202
|View full text |Cite
|
Sign up to set email alerts
|

Redes poliméricas de macromoléculas naturais como hidrogéis superabsorventes

Abstract: New hydrogels based on natural macromolecules such as gellan gum, chitosan, alginate, gelatin and lysine were synthetized and characterized by spectroscopic, thermal and microscopic analysis. The samples were also investigated in terms of water absorption and fertilizers release. The samples were obtained by crosslinking reactions of gellan gum (GGHA and GGLA) with (i) chitosan ( For the sample GGHA:CH the water retention time was 100% higher and about 60% higher for the hydrogels GGHA:LYS, GGHA:JEF and GGHA:G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
4
0
4
Order By: Relevance
“…Hydrogels, also known as hydroabsorbent polymers or water-retaining gels, are capable of absorbing and retaining large amounts of water and/or biological fluids, due to their chemically or physically crosslinked hydrophilic polymer networks (BRITO et al 2013), which change with hydration as shown in Figure 1, modified from Sabadini (2015). Aouada et al (2009) define such polymers as hydrophilic systems formed by two or more components joined by covalent and/or electrostatic bonds arranged in one or more three-dimensional structured networks surrounded by molecules of a given solvent, generally water.…”
Section: Composition and Purposementioning
confidence: 99%
See 4 more Smart Citations
“…Hydrogels, also known as hydroabsorbent polymers or water-retaining gels, are capable of absorbing and retaining large amounts of water and/or biological fluids, due to their chemically or physically crosslinked hydrophilic polymer networks (BRITO et al 2013), which change with hydration as shown in Figure 1, modified from Sabadini (2015). Aouada et al (2009) define such polymers as hydrophilic systems formed by two or more components joined by covalent and/or electrostatic bonds arranged in one or more three-dimensional structured networks surrounded by molecules of a given solvent, generally water.…”
Section: Composition and Purposementioning
confidence: 99%
“…Devido a isso, os polímeros hidroabsorventes podem ser utilizados na atividade agrícola como condicionadores de solo, aumentando a capacidade de armazenamento de água e a retenção de nutrientes, reduzindo o número de irrigações, a perda de nutrientes e custos de produção (SAAD et al, 2009). Sabadini (2015). Figura 1 -Hidrogel natural produzido a partir do intercruzamento de goma gelana liofilizada (A) e não liofilizada (B) com aumento de 300x em microscópio eletrônico de varredura.…”
Section: Composição E Finalidadesunclassified
See 3 more Smart Citations